A Light‐Hole Germanium Quantum Well on Silicon. Issue 27 (2nd June 2022) - Assali, Simone; Attiaoui, Anis; Vecchio, Patrick Del; Mukherjee, Samik; Nicolas, Jérôme; Moutanabbir, Oussama
Abstract: The quiet quantum environment of holes in solid‐state devices is at the core of increasingly reliable architectures for quantum processors and memories. However, due to the lack of scalable materials to properly tailor the valence band character and its energy offsets, the precise engineering of light‐hole (LH) states remains a serious obstacle toward coherent optical photon–spin interfaces needed for a direct mapping of the quantum information encoded in photon flying qubits to stationary spin processors. Herein, to alleviate this long‐standing limitation, an all‐group‐IV low‐dimensional system is demonstrated, consisting of a highly tensile strained germanium quantum well grown on silicon allowing new degrees of freedom to control and manipulate the hole states. Wafer‐level, high bi‐isotropic in‐plane tensile strain (<1%) is achieved using strain‐engineered, metastable germanium–tin alloyed buffer layers yielding quantum wells with LH ground state, high g ‐factor anisotropy, and a tunable splitting of the hole sub‐bands. The epitaxial heterostructures display sharp interfaces with sub‐nanometer broadening and show room‐temperature excitonic transitions that are modulated and extended to the mid‐wave infrared by controlling strain and thickness. This ability to engineer quantum structures with LH selective confinement and controllable optical response enables manufacturable silicon‐compatible platforms relevant to integrated quantum communication and sensing technologies. Abstract : Silicon‐integrated light‐hole quantum wells: a versatile platform toward coherent optical photon–spin interfaces for a direct mapping of the quantum information encoded in photon flying qubits to stationary spin processor is reported.